Public Preferences for Traditional Chinese Medicine and Conventional Treatment for Low Back Pain in Salatiga District, Sambas Regency - Suryadi Suryadi (Journal of World Science, 2024)
Lower back pain is a common health issue affecting many individuals worldwide, often leading to significant discomfort and reduced quality of life. Understanding patients' preferences for treatment options is crucial in providing adequate healthcare. This study analyzes the factors influencing patient preferences between Traditional Chinese Medicine (TCM) and conventional medicine for treating lower back pain in Salatiga District, Sambas Regency. A quantitative approach using surveys and Structural Equation Modeling (SEM) was employed, gathering data from 50 patients who had utilized either TCM or conventional medicine. Results indicate that treatment effectiveness, economic factors, perceptions of treatment, accessibility, and continuity of care significantly influence patient choices. Treatment effectiveness emerged as the most critical factor, with patients opting for the most effective pain relief methods. Economic considerations, including treatment costs and insurance coverage, were vital. This study highlights the need for inclusive health policies that support access to TCM and conventional medicine, aiming to improve patient education and integrate these treatment options into the healthcare system.